Innovation development of enterprises of the coal industry: problems and directions of providing - Zaloznova, Yuliia (Skhid, 2013)
Requirements for activization of innovative activity in the coal industry are defined. The reasons, which create barriers for innovation development of the coal industry, are proved. The international experience of introduction of innovations at the coal enterprises is considered. Offers of overcoming of innovation development obstacles at the state, branch and industrial levels of management are given.